Korean wave in Malaysia: A study on purchasing behaviour of Malaysian youth - Tan, Xuan Ni (2023)
The popularity of Korean Wave has a great impact on audience’s behaviour, attitudes and intentions. The global Korean wave has had a significant impact on brand marketing. Therefore, it is important to study on the consumer purchasing behaviour. This study focuses on the purchasing behaviour of buying Korean products among Malaysian youth. Hence, this study uses quantitative survey to study the influence of Korean Wave and factors of purchase decision making among them. An online survey questionnaire is designed and distributed to 50 Malaysian youth aged between 18 to 28 years old, who experienced Korean Wave before through Google form. The major finding of this study is Korean Wave influence people positively in terms of behaviour and thoughts. In terms of buying behaviour, one of the significant result is idol effect has great impacts on consumers to buy Korean goods. The taste of Korean food is important as consumers consider to purchase Korean food because the food is tasty and suits their taste buds. While buying beauty products, consumers concern on the quality, satisfaction, and good reputation of the brands the most.